Implementasi Metode Accrual Basis dalam Sistem Informasi Akuntansi Arus Kas - Ahmad Ashifuddin aqham; Bagus Sudirman (Universitas Sains dan Teknologi Komputer, 2020)
A cash flow statement is a financial report that contains information on cash inflows and cash outflows from a company during a certain period. This information is presented according to the type of activity that causes the cash inflows and outflows to occur. Company activities generally consist of three types, namely, operational activities, investment activities and financial activities. The process of receiving and disbursing cash is also recorded at any time for the preparation of the company's income statement. Cash flow recording activities at this company are still manual where every company receipt will be recorded by employees of the finance department which will ultimately be recapitulated in the annual report and compared with other recording results such as cash disbursements. This system has many weaknesses where the information needed cannot be presented quickly and accurately, requiring a fairly complicated process for a longer time to check certain cash flows.